If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -7x = 7x + 37 Reorder the terms: 9 + -7x = 37 + 7x Solving 9 + -7x = 37 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 9 + -7x + -7x = 37 + 7x + -7x Combine like terms: -7x + -7x = -14x 9 + -14x = 37 + 7x + -7x Combine like terms: 7x + -7x = 0 9 + -14x = 37 + 0 9 + -14x = 37 Add '-9' to each side of the equation. 9 + -9 + -14x = 37 + -9 Combine like terms: 9 + -9 = 0 0 + -14x = 37 + -9 -14x = 37 + -9 Combine like terms: 37 + -9 = 28 -14x = 28 Divide each side by '-14'. x = -2 Simplifying x = -2
| 12/a=132/35 | | 3cosx+4=5cosx+5 | | 5cosx=-5sinx | | u/5=5.7 | | -6(x+4)=8(x-4) | | 2/11=4/t-1 | | 4/5x5/9 | | x+x(.1)=150000 | | 1x^2-8+6y^3+3y-12x=2 | | 2+3x=7x-22 | | 3/6h=12/72 | | 8(6n-6)=7-7n | | -4(-2x+5)=9x | | 4/7y-1/3=1/5 | | 785+86= | | (2x+5)=6x+15 | | -2(3x+2)=-14x-2 | | 6x+8=3x+2 | | -388=7(7r+1)-3 | | -14+17=-3(x+8) | | y=34-0.5x | | 2(m-3)+5=19 | | Sen(2x)-2*cosx=0 | | -8n+3=-5n-6 | | -6k+k^2=7 | | 27-6k=3(6k+1) | | 2x+11=3x-7 | | F=23 | | 14=4w+6 | | 7/10=28/x | | 6-5x=-2-3x | | 54x^2-3x-40=0 |